SDF-1/CXCR4/CXCR7 is pivotal for vascular smooth muscle cell proliferation and chronic allograft vasculopathy - Thomas, Michael Nikolaus; Kalnins, Aivars; Andrassy, Martin; Wagner, Anne; Klussmann, Sven; Rentsch, Markus; Habicht, Antje; Pratschke, Sebastian; Stangl, Manfred Johannes; Bazhin, Alexandr V.; Meiser, Bruno; Fischereder, Michael; et al. (Transplant international, 2015)
Chronic rejection remains a major obstacle in transplant medicine. Recent studies suggest a crucial role of the chemokine SDF-1 on neointima formation after injury. Here, we investigate the potential therapeutic effect of inhibiting the SDF-1/CXCR4/CXCR7 axis with an anti-SDF-1 Spiegelmer (NOX-A12) on the development of chronic allograft vasculopathy. Heterotopic heart transplants from H-2bm12 to B6 mice and aortic transplants from Balb/c to B6 were performed. Mice were treated with NOX-A12. Control animals received a nonfunctional Spiegelmer (revNOX-A12). Samples were retrieved at different time points and analysed by histology, RT-PCR and proliferation assay. Blockade of SDF-1 caused a significant decrease in neointima formation as measured by intima/media ratio (1.0 ± 0.1 vs. 1.8 ± 0.1, P < 0.001 AoTx; 0.35 ± 0.05 vs. 1.13 ± 0.27, P < 0.05 HTx). In vitro treatment of primary vascular smooth muscle cells with NOX-A12 showed a significant reduction in proliferation (0.42 ± 0.04 vs. 0.24 ± 0.03, P < 0.05). TGF-β, TNF-α and IL-6 levels were significantly reduced under SDF-1 inhibition (3.42 ± 0.37 vs. 1.67 ± 0.33, P < 0.05; 2.18 ± 0.37 vs. 1.0 ± 0.39, P < 0.05; 2.18 ± 0.26 vs. 1.6 ± 0.1, P < 0.05). SDF-1/CXCR4/CXCR7 plays a critical role in the development of chronic allograft vasculopathy (CAV). Therefore, pharmacological inhibition of SDF-1 with NOX-A12 may represent a therapeutic option to ameliorate chronic rejection changes.